A systematic review of tobacco smoking cessation services in Africa: Practices and challenges faced by healthcare workers - Ilesanmi, Olayinka Stephen; Agwai, Victoria Ifeoma; Afolabi, Aanuoluwapo Adeyimika (Journal of Ideas in Health, 2021)
Background: Tobacco smoking is a global public health challenge, resulting in an estimated loss of 1.4 trillion United States Dollars (USD), a preventable risk that can be achieved through tobacco cessation services. The study, therefore, aimed to review the most frequently used methods employed by healthcare workers (HCWs) in providing tobacco cessation services and reported challenges in Africa. Methods: A systematic review was conducted using five electronic databases (PubMed, Base, PsychInfo, Google Scholar, and African Journal Online) for published studies on HCW’s practices and challenges on tobacco cessation in Africa. We adopted a three-stage methodology to conduct the study, which identified articles using pre-defined key terms, screened articles to remove duplicates, and excluded irrelevant articles after reading the manuscripts’ titles and abstracts. Results: We reviewed articles and found that 35.0% to 83.0% of HCWs frequently asked their patients to quit smoking. Also, 14.9% of HCWs assisted smoking cessation among their patients, among whom 3.9% prescribed oral depressants and 2.8% prescribed Nicotine Replacement Therapy (NRT). Further, 17.0% of HCWs had guidelines to help patients to cease smoking. Challenges were lack of efficacy and training, lack of system support, low sense of responsibility by some physicians to incorporate the smoking cessation therapy to their patients, lack of attractive educational resources on smoking cessation, limited knowledge on effective intervention strategies, lack of guidelines, lack of specialists for smoking cessation, and unavailability of NRT. Conclusion: Follow-up should be commenced and intensified by HCWs for smoking cessation among tobacco smokers.